Insomnia Symptoms Moderate the Relationship Between Perseverative Cognition and Backward Inhibition in the Task-Switching Paradigm - Ballesio, Andrea; Cerolini, Silvia; Vacca, Mariacarolina; Lucidi, Fabio; Lombardo, Caterina (Frontiers in Psychology, 2020)
Perseverative cognition (PC), i.e., the continuous cognitive representation of uncontrollable threats, is known to dampen executive control processes in experimental paradigms. Similarly, PC has been shown to impair sleep and to be implicated in the exacerbation of insomnia, which may in turn contribute to the disruption of executive functions. The interactions between PC and insomnia in influencing executive functions, however, has never been tested to date. In the present study we explored whether insomnia symptoms may moderate the associations between PC and disrupted executive functions, with the hypothesis to find a stronger relationship between these variables at increasing levels of insomnia. Fifty participants completed measures of trait PC and insomnia severity in the previous month and also completed a computerized task switching paradigm assessing backward inhibition, switch cost and accuracy. Prior to the task switching, participants completed a measure of state rumination in order to control for the effects of state PC on cognitive performance. Results show that trait PC was significantly correlated with higher insomnia symptoms and state rumination and marginally correlated with lower backward inhibition and longer switch cost. Moreover, insomnia severity moderated the relationship between trait PC and backward inhibition after controlling for the effects of state rumination; that is, the relationship between PC and inhibitory deficits was stronger in those with higher vs. lower levels of insomnia symptoms. Findings suggest the need to better elucidate the associations between PC, insomnia and executive functioning in clinical samples and longitudinal designs.